1993
DOI: 10.7863/jum.1993.12.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle sonography: a correlative study of echogenicity and morphology

Abstract: In skeletal muscle sonography high echogenicities have proved to be of diagnostic value. The following study examines whether these echointensities are caused mainly by interstitial fat or fibrosis. Consequently, the echogenicities of 86 muscles, their diameters, and the thickness of subcutaneous fat layers superficial to these muscles were measured and compared for content of fat and connective tissue, which were assessed by morphometry and biochemical testing in the corresponding muscle biopsy samples. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
258
3
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(274 citation statements)
references
References 3 publications
6
258
3
7
Order By: Relevance
“…The advantages of US are that it is noninvasive as well as less expensive and more portable than other medical imaging modalities such as magnetic resonance imaging, computed tomography, and dual-energy X-ray absorptiometry. The reliability and validity of MT and EI have been confirmed in the literature [19,21,24,26,28,29]. MT is positively associated with the muscle size and is thus used as an index of muscle quantity [24,25].…”
mentioning
confidence: 59%
“…The advantages of US are that it is noninvasive as well as less expensive and more portable than other medical imaging modalities such as magnetic resonance imaging, computed tomography, and dual-energy X-ray absorptiometry. The reliability and validity of MT and EI have been confirmed in the literature [19,21,24,26,28,29]. MT is positively associated with the muscle size and is thus used as an index of muscle quantity [24,25].…”
mentioning
confidence: 59%
“…There is also an increase in body fat [13]. Normally, subcutaneous fat, water and skeletal muscle fibres are hypoechoeic, but infiltration of skeletal muscles by fat results in increased muscular EI [15]. This may be due to a change in acoustic impedance at the surface of the fat cells and an increase in scattering of the ultrasound energy by the intramuscular fat.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that muscle ultrasound can be of value in the diagnosis of neuromuscular disorders by making it possible to reliably assess muscle thickness and objectify muscle atrophy (or hypertrophy) [12,33,36,37]. Besides muscle atrophy changes in muscle morphology can also be visualized with ultrasound.…”
Section: Muscle Ultrasound In Neuromuscular Disordersmentioning
confidence: 99%
“…a muscle becomes whiter in appearance [11,13,36]. It is thought that the replacement of muscle tissue with fat and fibrosis is the main cause of increased muscle echo intensity, as they increase the number of reflections within the muscle and therefore the mean grey value of the muscle in the ultrasound image (Fig 3) [29,35,37]. Markedly increased muscle echo intensity can easily be detected visually (Fig 7).…”
Section: Muscle Ultrasound In Neuromuscular Disordersmentioning
confidence: 99%